Antimicrobial Activity of Moxifloxacin 4th Generation Quinolones Against H-Pylori in Tertiary Care Hospital Peshawar - Zakia Subhan, Furqan Ali Shah, Hassan Farooq, Syed Hasnain Ali Shah, Mizhgan Ovais Khan, Erum Rehman, Khadija Raziq, Safdar Ali, Sudhair Abbas Bangash, Inam-U-Llah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of current study was to evaluate effectiveness of moxifloxacin 4th generation quinolones against patients of H-pylori infection admitted in a tertiary care hospital Peshawar. Study Design:Observational study Place and Duration: This study was carried out at Khyber Teaching Hospital, Peshawar from December 2021 to February 2022 Methods: There were 180 patients of both genders had age 18-55 years with H-pylori infection were included. After obtaining informed written consent detailed demographics of all cases were recorded. Patients were equally divided in two groups. Group I received 400mg moxifloxacin for 6-days and group II received moxifloxacin for 12-days. All the patients received 1000mg amoxicillin and lansoprazole 30 mg twice day. Posttreatment results were compared in terms of eradication rate and complications among both groups. Results:We found that 105 (58.3%) patients were males and 75 (41.7%) patients were females. Mean age of the patients was 47.6±11.74 years and had mean BMI 25.8±12.34 kg/m2. Majority of the patients 98 (54.4%) were smokers. Most common comorbidity was hypertension found in 62 (34.4%) cases, diabetes mellitus in 42 (23.3%) cases, chronic pulmonary disease in 28 (15.6%) and ischemic heart disease in 13 (7.2%) cases. We found that eradication rate among cases of group I was lower found in 59 (65.6%) cases compared to group II found in 80 (88.9%) cases with p value <0.005. Most common complications were diarrhea, nausea, abdominal pain and dizziness but their frequency was higher in group II but difference was insignificant. Conclusion: We concluded in this study that the use of moxifloxacin4th generation quinolones against H-Pyloriinfection for 12-days in reduction of disease severity and higher eradication rate as compared to 7-days treatment. Complications were higher in 10-days of treatment because of excess usage of regular antibiotics but found no any significant difference to 7-days treatment. Keywords: Eradication rate, H-pylori, Complications, Moxifloxacin